2021
DOI: 10.1177/21582440211004934
|View full text |Cite
|
Sign up to set email alerts
|

Belief Change Before and After the Teaching Practicum Among Chinese Pre-Service ELT Teachers

Abstract: This article aims to study the dynamic change of teachers’ beliefs among pre-service teachers. A longitudinal design was adopted to investigate English language teaching (ELT) pre-service teachers’ belief change after a 3-month teaching practicum by administering pretest and posttest questionnaires, semistructured interviews, and reflective journals. Repeated measures and paired sample t-test analyses showed significant differences across different aspects of beliefs in all the participants, but belief changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 69 publications
(79 reference statements)
1
13
0
Order By: Relevance
“…The experiment revealed that language and visual art integrated teaching provides input through listening and reading, without the assistance of pictures. The composition of pictures was stimulated by language and comprehended, induced, and transformed into individually perceived concepts (Qiu et al, 2021). Ethnic minority students were trained in terms of concentration, quick thinking, ideation, memory, and emotional perception through listening to ensure proper judgment and analysis in the listening process.…”
Section: Discussionmentioning
confidence: 99%
“…The experiment revealed that language and visual art integrated teaching provides input through listening and reading, without the assistance of pictures. The composition of pictures was stimulated by language and comprehended, induced, and transformed into individually perceived concepts (Qiu et al, 2021). Ethnic minority students were trained in terms of concentration, quick thinking, ideation, memory, and emotional perception through listening to ensure proper judgment and analysis in the listening process.…”
Section: Discussionmentioning
confidence: 99%
“…In the Chinese context, English is a compulsory subject for different levels of students from primary schools to universities. Across the country, there are more than 160 ''Normal'' (teacher training) universities or colleges where EFL teachers' training programs are set up in different levels (Qiu et al, 2021). In the 4-year university programs, the EFL major students are required to finish two main parts of courses: English knowledge/ skills and English teaching pedagogical courses/practices.…”
Section: The Current Focusmentioning
confidence: 99%
“…For example, a research project on secondary pre-service teachers’ responsibility to care for students found that neither pedagogy nor discipline strategies would be effective without care, which raises training implications and suggestions for future research into training these teachers (Laletas & Reupert, 2016). Attention to pre-service teacher education is growing, including to pre-service teachers in specific fields such as pre-service teachers involved in teaching bilingual students or English as a foreign language (Lummis et al, 2015; Qiu et al, 2021). Pre-service teachers’ critical reflections on lessons taught during practice teaching are analyzed to assess how they put their theories into teaching practice (Heeralal, 2014).…”
Section: Research Literature On Pre-service Teachersmentioning
confidence: 99%